Selected essays on opera - Weisstein, Ulrich (Word and music studies ;, 2006)
"Ulrich Weisstein, an international authority in the fields of comparative literature and comparative arts, has been a pioneer paving the way for present-day intermedia studies. Among his broad intermedial interests opera has always held a central place. For the first time this volume makes available his major contributions to opera criticism in compact form, thus meeting a serious scholarly demand." "The necessarily stringent selection of essays from Professor Weisstein's large output on opera, reflecting fifty years of involvement with the genre, is primarily governed by the wish to present texts that are representative of their author's work and, at the same time, are unlikely to be readily available through other channels. The fourteen essays collected are arranged in chronological order, some of them showing Ulrich Weisstein as an initiator of librettology, others tracing adaptive processes extending from textual sources to final operas, or investigating writer/composer collaborations."--Jacket